Handle with care I

Calculus Level 3

If the closed form of m = 1 n = 0 ( 1 ) m ( 2 m + n ) 2 = G a c π a b \sum_{m=1}^{\infty} \sum_{n=0}^{\infty} \dfrac{(-1)^m}{(2m+n)^2} = \dfrac{G}{a} - \dfrac{c\pi^a}{b} where a a and c c are primes. Find the value of a + b + c a+b+c .

Notation : G G is Catalan's constant .

This is an original and modified version of Handle with care II . It would be better to solve problem without integration.


The answer is 37.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

S = m = 1 n = 0 ( 1 ) m ( 2 m + n ) 2 = 1 2 2 1 3 2 1 4 2 1 5 2 1 6 2 1 7 2 for m = 1 + 1 4 2 + 1 5 2 + 1 6 2 + 1 7 2 + 1 8 2 + 1 9 2 + for m = 2 1 6 2 1 7 2 1 8 2 1 9 2 1 1 0 2 1 1 1 2 for m = 3 + = 1 2 2 1 3 2 1 6 2 1 7 2 1 1 0 2 1 1 1 2 \begin{aligned} S & = \sum_{m=1}^\infty \sum_{n=0}^\infty \frac {(-1)^m}{(2m+n)^2} \\ & = - \frac 1{2^2} - \frac 1{3^2} - \frac 1{4^2} - \frac 1{5^2} - \frac 1{6^2} - \frac 1{7^2} - \cdots & \small \blue{\text{for } m = 1} \\ & \quad + \frac 1{4^2} + \frac 1{5^2} + \frac 1{6^2} + \frac 1{7^2} + \frac 1{8^2} + \frac 1{9^2} + \cdots & \small \blue{\text{for } m = 2} \\ & \quad - \frac 1{6^2} - \frac 1{7^2} - \frac 1{8^2} - \frac 1{9^2} - \frac 1{10^2} - \frac 1{11^2} - \cdots & \small \blue{\text{for } m = 3} \\ & \quad + \cdots \\ & = - \frac 1{2^2} - \frac 1{3^2} - \frac 1{6^2} - \frac 1{7^2} - \frac 1{10^2} - \frac 1{11^2} - \cdots \end{aligned}

= ( 1 2 2 + 1 6 2 + 1 1 0 2 + ) + ( 1 3 2 1 7 2 1 1 1 2 ) = 1 2 2 ( 1 1 2 + 1 3 2 + 1 5 2 + 1 7 2 + ) + 1 2 [ ( 1 1 2 1 3 2 + 1 5 2 ) ( 1 1 2 + 1 3 2 + 1 5 2 + ) ] = 1 4 [ ( 1 1 2 + 1 2 2 + 1 3 2 + ) ( 1 2 2 + 1 4 2 + 1 6 2 + ) ] + 1 2 [ G ( 1 1 2 + 1 3 2 + 1 5 2 + ) ] where G denotes the Catalan’s constant. = 1 4 [ ( 1 1 2 + 1 2 2 + 1 3 2 + ) 1 2 2 ( 1 1 2 + 1 2 2 + 1 3 2 + ) ] + 1 2 [ G ( 1 1 2 + 1 3 2 + 1 5 2 + ) ] = 1 4 [ ζ ( 2 ) 1 4 ζ ( 2 ) ] + 1 2 [ G 3 4 ζ ( 2 ) ] where ζ ( ) denotes the Riemann zeta function = G 2 9 ζ ( 2 ) 16 = G 2 3 π 2 32 and ζ ( 2 ) = π 2 6 \begin{aligned} \ \ \ & = \small - \blue{\left(\frac 1{2^2} + \frac 1{6^2} + \frac 1{10^2} + \cdots \right)} + \red{\left(-\frac 1{3^2} - \frac 1{7^2} - \frac 1{11^2} - \cdots \right)} \\ & = \small - \blue{\frac 1{2^2} \left(\frac 1{1^2} + \frac 1{3^2} + \frac 1{5^2} + \frac 1{7^2} + \cdots \right)} \\ & \quad \small + \red{\frac 12 \left[\left(\frac 1{1^2} - \frac 1{3^2} + \frac 1{5^2} - \cdots \right)-\left(\frac 1{1^2} + \frac 1{3^2} + \frac 1{5^2} + \cdots \right)\right]} \\ & = \small - \blue{\frac 14 \left[\left(\frac 1{1^2} + \frac 1{2^2} + \frac 1{3^2} + \cdots \right)-\left(\frac 1{2^2} + \frac 1{4^2} + \frac 1{6^2} + \cdots \right)\right]} \\ & \quad \small + \red{\frac 12 \left[G-\left(\frac 1{1^2} + \frac 1{3^2} + \frac 1{5^2} + \cdots \right)\right]} & \small \red{\text{where }G \text{ denotes the Catalan's constant.}} \\ & = \small - \blue{\frac 14 \left[\left(\frac 1{1^2} + \frac 1{2^2} + \frac 1{3^2} + \cdots \right)- \frac 1{2^2} \left(\frac 1{1^2} + \frac 1{2^2} + \frac 1{3^2} + \cdots \right)\right]} \\ & \quad \small + \red{\frac 12 \left[G-\left(\frac 1{1^2} + \frac 1{3^2} + \frac 1{5^2} + \cdots \right)\right]} \\ & = - \blue{\frac 14 \left[\zeta (2) - \frac 14 \zeta(2)\right]} + \red{\frac 12 \left[G-\frac 34 \zeta(2) \right]} & \small \blue {\text{where }\zeta (\cdot) \text{ denotes the Riemann zeta function}} \\ & = \frac G2 - \frac {9\blue{\zeta(2)}}{16} = \frac G2 - \frac {3\pi^2}{32} & \small \blue{\text{and }\zeta(2) = \frac {\pi^2}6} \end{aligned}

Therefore, a + b + c = 2 + 32 + 3 = 37 a+b+c = 2+32+3 = \boxed{37} .


References:

Naren Bhandari
Oct 6, 2019

Here I wish to share my solution without integration

m = 1 n = 0 ( 1 ) m ( 2 m + n ) 2 = m = 1 ( 1 ) m n = 0 1 ( 2 m + n ) 2 \sum_{m=1}^{\infty} \sum_{n=0}^{\infty} \dfrac{(-1)^m}{(2m+n)^2}=\sum_{m=1}^{\infty}(-1)^m\sum_{n=0}^{\infty}\dfrac{1}{(2m+n)^2} if we write the inner sum in series form we notice that n = 0 1 ( 2 m + n ) 2 = 1 4 n = 0 1 ( m + n ) 2 S 1 + n = 1 , 3 , 5 1 ( 2 m + n ) 2 S 2 \sum_{n=0}^{\infty} \dfrac{1}{(2m+n)^2}= \underbrace{\dfrac{1}{4}\sum_{n=0}^{\infty} \dfrac{1}{(m+n)^2} }_{\text{}S_1}+\underbrace {\sum_{n=1,3,5\cdots}^{\infty} \dfrac{1}{(2m+n)^2}}_{\text{} S_2} and hence have m = 1 n = 0 ( 1 ) m ( 2 m + n ) 2 = m = 1 ( 1 ) m 1 4 n = 0 1 ( m + n ) 2 S 1 + m = 1 ( 1 ) m n = 1 , 3 , 5 1 ( 2 m + n ) 2 S 2 \sum_{m=1}^{\infty} \sum_{n=0}^{\infty} \dfrac{(-1)^m}{(2m+n)^2}=\sum_{m=1}^{\infty}(-1)^m \underbrace{\dfrac{1}{4}\sum_{n=0}^{\infty} \dfrac{1}{(m+n)^2} }_{\text{}S_1}+\sum_{m=1}^{\infty} (-1)^m\underbrace {\sum_{n=1,3,5\cdots }^{\infty} \dfrac{1}{(2m+n)^2}}_{\text{} S_2} ] we now evaluate the S 1 S_1 and S 2 S_2 separately as follows 4 S 1 = m = 1 n = 0 ( 1 ) m ( m + n ) 2 = m = 1 ( 1 ) m ( 1 m 2 + 1 ( m + 1 ) 2 ) + m = 1 ( 1 ) m ( 1 ( m + 2 ) 2 + 1 ( m + 3 ) 2 ) + = m = 1 ( 1 ( m + 1 ) 2 1 m 2 ) Telescopes + m = 1 ( 1 ( m + 3 ) 2 1 ( m + 2 ) 2 ) Telescopes + = ( 1 1 2 + 1 3 2 + 1 5 2 + ) = m = 1 1 ( 2 m 1 ) 2 = ( m = 1 1 m 2 1 4 m = 1 1 m 2 ) = π 2 8 \begin{aligned}4S_1&=\sum_{m=1}^{\infty} \sum_{n=0}^{\infty}\dfrac{(-1)^m}{(m+n)^2}=\sum_{m=1}^{\infty} (-1)^m\left(\dfrac{1}{m^2}+\dfrac{1}{(m+1)^2}\right)\\ &+\sum_{m=1}^{\infty}(-1)^m \left(\dfrac{1}{(m+2)^2}+\dfrac{1}{(m+3)^2}\right)+\cdots \\&=\underbrace{\sum_{m=1}^{\infty} \left(\dfrac{1}{(m+1)^2}-\dfrac{1}{m^2}\right)}_{\text {Telescopes}}+\underbrace{\sum_{m=1}^{\infty} \left(\dfrac{1}{(m+3)^2}-\dfrac{1}{(m+2)^2}\right)}_{\text {Telescopes}}+\cdots \\ &=-\left(\dfrac{1}{1^2}+\dfrac{1}{3^2}+\dfrac{1}{5^2}+\cdots \right) =-\sum_{m=1}^{\infty}\dfrac{1}{(2m-1)^2}\\&=-\left(\sum_{m=1}^{\infty}\dfrac{1}{m^2}-\dfrac{1}{4}\sum_{m=1}^{\infty}\dfrac{1}{m^2}\right)=-\dfrac{\pi^2}{8}\end{aligned} therefore we have S 1 = π 2 32 S_1=-\frac{\pi^2}{32} and we are left to evaluate S 2 = m = 1 n = 1 , 3 , 5 ( 1 ) m ( 2 m + n ) 2 = m = 1 ( 1 ) m ( 1 ( 2 m + 1 ) 2 + 1 ( 2 m + 3 ) 2 ) + m = 1 ( 1 ) m ( 1 ( 2 m + 5 ) 2 + 1 ( 2 m + 7 ) 2 ) + = m = 1 ( 1 ( 2 m + 3 ) 2 1 ( 2 m + 1 ) 2 ) Telescopes + m = 1 ( 1 ( 2 m + 7 ) 2 1 ( 2 m + 5 ) 2 ) Telescopes + = ( 1 3 2 + 1 7 2 + 1 1 1 2 + ) = m = 0 1 ( 4 m + 3 ) 2 = 1 4 2 ψ 1 ( 3 4 ) = 1 16 ( π 2 8 G ) \begin{aligned} S_2=& \sum_{m=1}^{\infty}\sum_{n=1,3,5\cdots }^{\infty}\dfrac{(-1)^m}{(2m+n)^2}=\sum_{m=1}^{\infty} (-1)^m\left(\dfrac{1}{(2m+1)^2}+\dfrac{1}{(2m+3)^2}\right)\\ &+\sum_{m=1}^{\infty}(-1)^m \left(\dfrac{1}{(2m+5)^2}+\dfrac{1}{(2m+7)^2}\right)+\cdots \\&=\underbrace{\sum_{m=1}^{\infty} \left(\dfrac{1}{(2m+3)^2}-\dfrac{1}{(2m+1)^2}\right)}_{\text {Telescopes}}+\underbrace{\sum_{m=1}^{\infty} \left(\dfrac{1}{(2m+7)^2}-\dfrac{1}{(2m+5)^2}\right)}_{\text {Telescopes}}+\cdots\\&=-\left(\dfrac{1}{3^2}+\dfrac{1}{7^2}+\dfrac{1}{11^2}+\cdots\right)=-\sum_{m=0}^{\infty}\dfrac{1}{(4m+3)^2}\\&=-\dfrac{1}{4^2} \psi^1\left(\dfrac{3}{4}\right) =-\dfrac{1}{16}\left(\pi^2-8G\right)\end{aligned} or m = 0 1 ( 4 m + 3 ) 2 = m = 1 1 m 2 ( m = 1 1 ( 2 m ) 2 + m = 1 1 ( 4 m 3 ) 2 ) = π 2 8 ( m = 0 ( 1 ) m ( 2 m 1 ) 2 + m = 0 1 ( 4 m + 3 ) 2 ) m = 0 1 ( 4 m + 3 ) 2 = π 2 2 × 8 G 2 \begin{aligned}\sum_{m=0}^{\infty}\dfrac{1}{(4m+3)^2}&= \sum_{m=1}^{\infty}\dfrac{1}{m^2}-\left(\sum_{m=1}^{\infty}\dfrac{1}{(2m)^2}+\sum_{m=1}^{\infty}\dfrac{1}{(4m-3)^2}\right)\\&= \dfrac{\pi^2}{8}- \left(\sum_{m=0}^{\infty}\dfrac{(-1)^m}{(2m-1)^2}+\sum_{m=0}^{\infty}\dfrac{1}{(4m+3)^2}\right)\\&\implies \sum_{m=0}^{\infty}\dfrac{1}{(4m+3)^2} =\dfrac{\pi^2}{2\times 8}-\dfrac{G}{2} \end{aligned} thus m = 1 n = 0 ( 1 ) m ( 2 m + n ) 2 = π 2 32 + G 2 π 2 16 = G 2 3 π 2 32 \sum_{m=1}^{\infty} \sum_{n=0}^{\infty} \dfrac{(-1)^m}{(2m+n)^2}=-\dfrac{\pi^2}{32}+\dfrac{G}{2}-\dfrac{\pi^2}{16} =\dfrac{G}{2} -\dfrac{3\pi^2}{32}
This solution is of Ali Shather

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...